2022
DOI: 10.1590/fst.88021
|View full text |Cite
|
Sign up to set email alerts
|

Structure and nutrition of dark chocolate with pequi mesocarp (Caryocar villosum (Alb.) Pers.)

Abstract: In response to consumer's claims, the aim of this study was the addition of lyophilized pequi mesocarp (pulp) in dark chocolate formulation to improve nutritional value. The lyophilized pequi mesocarp was analyzed and granulometry, centesimal composition, carotenoids, and scanning electron microscopy were verified. Lyophilized mesocarp was added (1.5%) (F2) to the dark chocolate (F1) formulation, and particle size, temper index, physicochemical parameters, rheology, thermal analysis, total antioxidant capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…By contrast, the contents of TS and RS in T2 and T3 groups were improved. It was reported that high concentration of carbohydrates was naturally present in coffee and cocoa (Lorenzo et al, 2022;Mostafa, 2022). Thus, CTLs fermented with coffee and cocoa would show a relatively good performance on the sweetness and aroma richness.…”
Section: Conventional Chemical Compositions Analysismentioning
confidence: 99%
“…By contrast, the contents of TS and RS in T2 and T3 groups were improved. It was reported that high concentration of carbohydrates was naturally present in coffee and cocoa (Lorenzo et al, 2022;Mostafa, 2022). Thus, CTLs fermented with coffee and cocoa would show a relatively good performance on the sweetness and aroma richness.…”
Section: Conventional Chemical Compositions Analysismentioning
confidence: 99%
“…Reports such as that by Mejía et al (2021) show that, in Peruvian varieties of cocoa beans and chocolates, there are significant differences in their chemical and sensory characteristics, making it necessary to investigate techniques such as THz to identify them quickly. This type of spectroscopy will allow improving identification, especially in chocolates, with substitution or addition of ingredients that physicochemically show great differences (Lorenzo et al, 2022), and that need the development of modern techniques that allow their rapid and non-destructive identification.…”
Section: Classification Of Chocolate According To Its Cocoa Percentag...mentioning
confidence: 99%
“… pequi mesocarp (pulp) was added in lyophilized form. Lorenzo et al (2022) elderberries (EFrE), elderflowers (EFlE), and chokeberries (ChFrE) plant extract To enrich the functional properties of dark chocolate. The dried plant extract was used for fortification.…”
Section: Approaches To Fortify Dark Chocolatementioning
confidence: 99%
“…The phenolic content of the fortified chocolate was increased from 235.98 μg GAE mL −1 to 813.49 μg GAE mL −1 . In this study, lyophilization was chosen for the preservation of existing nutritional qualities ( Lorenzo et al, 2022 ).…”
Section: Approaches To Fortify Dark Chocolatementioning
confidence: 99%
See 1 more Smart Citation